To Know Through Touch: Sacramental Wisdom and Erotic Holiness in the Gospel of Philip - Kotzé, Zacharias (Diakrisis, 2025)
This article explores the conceptual metaphor of intimacy as epistemic access in the Gospel of Philip, where erotic union functions as a sacramental pathway to divine knowledge. Drawing on cognitive linguistics and Gnostic theology, the study examines how metaphors of touch, fusion, and bodily presence encode a form of "wisdom through embodiment." The Gospel of Philip frames holiness not as moral purity or ascetic withdrawal, but as a relational mode of knowing - one that privileges proximity, vulnerability, and shared essence. The metaphorical structure of phrases such as "the bridal chamber" and "those who unite will receive light" suggests a mystical epistemology grounded in physicality and mutual recognition. By analysing these metaphors through the lens of Conceptual Metaphor Theory and sacramental phenomenology, the article argues that Gnostic holiness is not merely esoteric but deeply experiential. This reframing challenges dualistic readings of Gnostic texts and opens a dialogue between ancient mystical traditions and contemporary theories of embodied cognition. Ultimately, the study contributes to a broader understanding of how metaphors of intimacy can function as vehicles of theological insight, positioning erotic union as a site of wisdom and sanctification.